Interference in learning English: Grammatical errors in English essay writing among rural Malay secondary school students in Malaysia - Marlyna Maros; Tan, Kim Hua; Khazriyati Salehuddin (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
The purpose of this article is to present an analysis of interference effect, a factor that plays an important role in inhibiting the acquisition of English among young Malay learners in Malaysian schools. The data substantiating the discussion throughout this article came from an empirical study of errors in essays written by Form One students in six schools in Malaysia. The findings of the study show that despite having gone through six years of learning English in school environment, the learners are still having difficulty in using correct English grammar in their writings. The three most frequent errors are: 1) the use of articles, 2) subject-verb agreement, and 3) copula ‘be’